An assessment of the challenges facing opposition political parties in Zimbabwe to consolidate political power since independence (1980): case study, movement for democratic change (MDC-T). - Musekiwa, Emmanuel (Midlands State University, 2017)
This research was an assessment of the challenges that have bedeviled the success of the opposition political parties in Zimbabwe since independence (1980). Despite looking at the general context of opposition political parties, much reference has been made to the Movement for Democratic Change led by Morgan R. Tsvangirai (MDC-T) that came into the political lime light in the year 1999. Theories played a pivotal role in articulating the challenges. Both qualitative and quantitative methods were employed to amass information. The target population was the opposition political leaders, their supporters as well as general populace. About twenty (20) interviews were conducted where many respondents lamented on the degree of violence, intimidation and corruption ZANU PF is employing and the researcher at times made the use of native languages thus mainly Shona and Ndebele in interpretation of questions. These techniques helped the researcher in the sense that people were able to clearly express their mixed feeling without the barrier of language limitation. In some circumstance the researcher made use of interpreters to translate on his behalf on the Ndebele language. The information provided in this work made use of the theoretical models that replicates challenges facing opposition political parties. The researcher made use of tables and piecharts in presenting findings, and the information was analyzed and then summarized. The information gathered elaborated that though most of these challenges are as a result of external forces, some of these challenges facing opposition political are also self-inflicted. As a result the researcher had to proffer recommendations on what the opposition political parties should undertake like revolting attending national events such as the independence celebrations and heroes commemorations to address these challenges they are facing since the political independence of Zimbabwe in 1980 to date in order for them be able to improve how they handle their issues in a bid to attain political power.